MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA PURASARI, KECAMATAN LEUWILIANG, KABUPATEN BOGOR. - Thantawi, Tubagus Rifqy; Rizal, Muhammad; Firdaus, Herlan (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
This community service aims to design the right Sharia Microfinance Institution in Purasari Village, Leuwiliang District, Bogor Regency, West Java Province. The subject of this community service is the people of Purasari Village, most of whom are farmers and who need access to financing in accordance with sharia principles. In this community service, activities are carried out based on a participatory method, where the community is involved in every stage of institutional design, from the identification of needs to the implementation of the plan.). The result of this community service is the formation of the concept of a sharia microfinance institution that can provide financing services and business assistance for the local community. With this community service, it can be concluded that the existence of Sharia Microfinance Institutions in Purasari Village will have a positive impact on improving the economic welfare of the community and encouraging sustainable micro business growth.